Pengaruh Return on Asset dan Debt to Equity Ratio terhadap Kebijakan Dividen - Fauzan, Farhan Miftah; Zakaria, Heikal Muhammad; Okabrian, Soni (The Double Entry Journal, 2022)
This study aims to determine the effect of Return on Assets (ROA) and Debt to Equity Ratio (DER) on Dividend Policy. The research method used is quantitative method with a descriptive verification approach. Population in this research is manufacture industries subsector food and beverage companies listed on the IDX. Research periods from 2016 - 2019, and using purposive sampling for sample selection with the number of samples obtained 11 companies that meet the criteria, in total 44 data observation. Technique analysis using multiple linear regression, and the results indicates that partially ROA has a positive effect on Dividend Policy, DER has no effect on Dividend Policy.